ANALISIS SISTEM INFORMASI AKUNTANSI SIKLUS PENGELUARAN KAS PADA PT DAPUR SEHATI FOOD - Nanggala, Ardhya Yudistira Adi; Ihsan, Ahmat Muniril; Nurholifah, Siti; Putra, Dony Anugerah; Ramadhani, Alif Farhan; Rafliansyah, Mohammad Nanda; Septiana, Nur Laila (Relawan Jurnal Indonesia, 2025)
This study was conducted to determine the flow of the accounting information system in the cash disbursement cycle at PT Dapur Sehati Food. The main focus of the study is to describe the cash disbursement process that occurs in the company and identify the units involved in the cycle. This study uses a qualitative approach with a descriptive method, where data is collected through observation and documentation of the cash disbursement procedure in the company. The results of the study indicate that the cash disbursement cycle at PT Dapur Sehati Food consists of several stages, starting from purchase requests, receipt of goods, making payment documents, to the process of recording transactions in the accounting system. Each stage is carried out by sections that have their own roles, such as the warehouse section, finance section, and accounting section. This study provides a comprehensive overview of how the accounting information system plays a role in recording and managing the cash disbursement process in the company.